2016
DOI: 10.1541/ieejeiss.136.525
|View full text |Cite
|
Sign up to set email alerts
|

Control Methods for the Precise Brain Temperature Management in Selective Brain Hypothermia Therapy

Abstract: The mathematical simulations are provided for the development of devices and/or methods for medical brain hypothermal treatment. The mathematical model reflecting thermal property of human head was presented as a group of particles consisting of small nodes. By using our mathematical model of head, a new appropriate brain cooling pattern is proposed for the temperature control in selective brain hypothermia, when its temperature rises owing to the increasing productive and accumulating heat by brain injuries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 7 publications
3
11
0
Order By: Relevance
“…12, studies using mathematical models with continuous arrangement of regular tetrahedrons [1,13,14], same as in the present study, showed relatively good agreement between simulated and measured results for different algorithms of temperature control. 12, studies using mathematical models with continuous arrangement of regular tetrahedrons [1,13,14], same as in the present study, showed relatively good agreement between simulated and measured results for different algorithms of temperature control.…”
Section: Utility Of Simulations Using Regular Tetrahedral Coordinate supporting
confidence: 78%
See 4 more Smart Citations
“…12, studies using mathematical models with continuous arrangement of regular tetrahedrons [1,13,14], same as in the present study, showed relatively good agreement between simulated and measured results for different algorithms of temperature control. 12, studies using mathematical models with continuous arrangement of regular tetrahedrons [1,13,14], same as in the present study, showed relatively good agreement between simulated and measured results for different algorithms of temperature control.…”
Section: Utility Of Simulations Using Regular Tetrahedral Coordinate supporting
confidence: 78%
“…The proposed method was verified for dynamic models [1,2,9] and thermodynamic models [10,13,14]; the method combines a number of features advantageous for a wide variety of biomathematical simulations. Besides, continuous state distributions can be visualized because most of space is defined as computable domain.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations